An Empirical Study of the Effect of Multimedia Information Technology on College English Teaching - Xiaoyu Luo (Randwick International of Education and Linguistics Science Journal, 2020)
In college English teaching, educators often use multimedia information technology to carry out teaching activities and present the corresponding curriculum content in detail. Based on two semesters of analysis and investigation, this paper presents an empirical study on multimedia teaching in two courses of a non-English major in one Chinese college. The results show that multimedia teaching technology can effectively enhance college students' interest in English learning, stimulate their enthusiasm, enhance the interaction between teachers and students, and cultivate their autonomous learning ability. The research suggests that colleges and universities should strengthen the hardware support and software facilities of multimedia-assisted teaching to promote the significant improvement of students' language ability.